Distribution of the brown bear (Ursus arctos marsicanus) in the Central Apennines, Italy, 2005-2014 - CIUCCI, Paolo; Altea, Tiziana; Antonucci, Antonio; CHIAVERINI, LUCA; Croce, Antonio Di; Fabrizio, Mauro; Forconi, Paolo; Latini, Roberta; MAIORANO, Luigi; Monaco, Antonio; Morini, Paola; Ricci, Filomena; et al. (Associazione Teriologica Italiana, 2017)
Despite its critical conservation status, no formal estimate of the Apennine brown bear (Ursus arctos marsicanus) distribution has ever been attempted, nor a coordinated effort to compile and verify all recent occurrences has ever been ensured. We used 48331 verified bear location data collected by qualified personnel from 20052014 in the central Apennines, Italy, to estimate the current distribution of Apennine brown bears. Data sources included telemetry relocations, scats and DNA-verified hair samples, sightings, indirect signs of presence, photos from camera traps, and damage to properties. Using a grid-based zonal analysis to transform raw data density, we applied ordinary kriging and estimated a 4923 km2 main bear distribution, encompassing the historical stronghold of the bear population, and including a smaller (1460 km2) area of stable occupancy of reproducing female bears. National and Regional Parks cover 38.8% of the main bear distribution, plus an additional 19.5% encompassed by the Natura 2000 network alone. Despite some methodological and sampling problems related to spatial and temporal variation in sampling effort at the landscape scale, our approach provides an approximation of the current bear distribution that is suited to frequently update the distribution map. Future monitoring of this bear population would benefit from estimating detectability across a range on environmental and sampling variables, and from intensifying the collection of bear presence data in the peripheral portions of the distribution.